HUBUNGAN PERILAKU MEROKOK DENGAN KONSENTRASI BELAJAR PADA MAHASISWA/I UNIVERSITAS SUMATERA UTARA - Yardina Fauziah Harahap; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
This study raised the relationship between smoking behavior and the level of concentration in learning at North Sumatra University students. This study aims to find out how the relationship between smoking behavior and the concentration of learning in these students. The method used in this research is descriptive quantitative involving 30 students as research respondents which in practice is carried out by distributing questionnaires. Smoking is a behavior that burns tobacco products that are intended to be burned, smoked and/or inhaled including clove cigarettes, white cigarettes, cigars or other forms produced from the nicotina tabacum, nicotina rustica and other species or syntheses whose smoke contains nicotina and tar, with or without additives. Student achievement is essentially a reflection of learning endeavors. In general, the better the business of learning, the better the achievements. Of course this is inseparable from the factors that influence it, among others, interest, motivation, parental educational level, parental income level, and so forth. The variables studied were the independent variable (smoking behavior) and the dependent variable (learning achievement). The result of the chi-square get p value = 0,414, meaning that there is no meaningful relationship between smoking behavior and learning achievement in student at University of North Sumatera.